A COMPREHENSIVE STUDY ON LITERATURE EVIDENCE, CLINICAL STUDIES AND PRACTICES OF HERBAL DRUGS FOR DIABETIC NEUROPATHY AND CARDIOMYOPATHY - Shamim, Arshiya; Siddiqui, Hefazat Hussain; Mahmood, Tarique; Bagga, Paramdeep; Kumar, Ranjan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Diabetes mellitus is a worldwide epidemic disease that eventually advances to a chronic stage and affects different vital organs by intensifying the underlying pathological factors, and through the remodeling of the tissues by the generation of reactive oxygen species leading to the development of respective organ failure. Two such complications are painful neuropathy and cardiomyopathy; both of which are common and progressive complications of diabetes. The symptoms of peripheral neuropathy include tingling, burning, lancinating pain, hyperesthesia, and allodynia. The course of the disease progression may vary from intermittent, mild symptoms to severe chronic, and daily pain; which culminates into poor quality of life. Another complication of diabetes mellitus, diabetic cardiomyopathy, is defined as a ventricular dysfunction disorder that occurs in diabetic patients. The development of the disease is characterized by a hidden subclinical period, during which cellular, structural changes and abnormalities lead to diastolic dysfunction, followed by systolic dysfunction, and terminating into heart failure. Left ventricular hypertrophy, metabolic abnormalities, extracellular matrix changes, small vessel disease, cardiac autonomic neuropathy, insulin resistance, oxidative stress, and apoptosis are the most important pathological advancements that lead to diabetic cardiomyopathy. Various pharmaceutical agents from different pharmacological categories have been proposed for the symptomatic treatment of painful diabetic neuropathy; however, it is a herculean task to select a drug due to the wide range of choices and lack of consistent guidelines for treatment. Similarly, treatment of cardiomyopathy is based on the general therapeutic rules of management of heart failure and no specifications have yet been addressed for this condition. Therefore, more studies are required to improve our knowledge of these complex syndromes. From this perspective, this review is designed to delineate a general overview of neuropathy and cardiomyopathy, referring to the conventional therapies in use and possible unconventional, natural, herbal, and safe treatments for both the above-mentioned complications of diabetes.